Prospects for the UK economy. (August 2015) - Kirby, Simon; Carreras, Oriol; Meaning, Jack; Piggott, Rebecca; Warren, James
Abstract : The production of this forecast is supported by the Institute's Corporate Members: Bank of England, HM Treasury, Mizuho Research Institute Ltd, Office for National Statistics, Santander (UK) plc and by the members of the NiGEM users group.